2019
DOI: 10.1159/000495311
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Directs Migration, Enhances and Orients Cell Division and Upregulates the Chemokine Receptors CXCR4 and CXCR2 in Endothelial Cells

Abstract: Natural direct current electric fields (DC EFs) within tissues undergoing angiogenesis have the potential to influence vessel formation, but how they affect endothelial cells is not clear. We therefore quantified behaviours of human umbilical vein endothelial cells (HUVEC) and human microvasculature endothelial cells (HMEC) stimulated by EFsin vitro. Both cell types migrated faster and toward the cathode; HUVECs responded to fields as low as 50mV/mm, but the HMEC threshold was 100 mV/mm. Mitosis was stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 71 publications
(104 reference statements)
1
45
0
Order By: Relevance
“…In in vitro 3D-culture studies, Yang et al describes EStim as "promoting synergy" between cells and scaffold material [48]. Finally, it was shown that not only cell alignment, but also cell division plane, could be controlled by externally applied EStim [49,50], theoretically making it possible to control the direction of cellular expansion.…”
Section: Cell Alignmentmentioning
confidence: 99%
“…In in vitro 3D-culture studies, Yang et al describes EStim as "promoting synergy" between cells and scaffold material [48]. Finally, it was shown that not only cell alignment, but also cell division plane, could be controlled by externally applied EStim [49,50], theoretically making it possible to control the direction of cellular expansion.…”
Section: Cell Alignmentmentioning
confidence: 99%
“…Kanno et al [16] showed that EF-stimulated skeletal muscle cell culture medium augmented the growth of endothelial cells. Cunha et al [36] demonstrated that DC electrical stimulation at 150 mV/ mm and at 300 mV/mm had a promoting effect on the mitosis of HUVECs. Our present study in endothelial cells using 150 mV/mm EF strength stimulation shows that the EF enhances the endothelial cell proliferation rate by approximately 163%, in agreement with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly electric fields (EF) enhance CXCR2 expression in vascular endothelial cells. 23 Although a number of blood-derived cells show directed cell migration in response to small electrical fields (macrophages, monocytes, neutrophils and T cells 24,25 ), whether mast cells are electrosensitive and might accumulate focally at stimulation sites, is not known but is testable. However, if the EFs established by PBCS needles directed mast cell migration and regulated cytokine secretion and receptor expression as occurs in many other cell types, a mast cell-based explanation of the remarkable efficacy of PBCS in alleviating CH may emerge.…”
Section: Discussionmentioning
confidence: 99%